Readiness of Galileo PNT Service for NATO Operations Threats and Challenges - Alhosban, Ahmad (International Journal of Membrane Science and Technology, 2023)
In the domain of the Defense ICT-based technology: (Information and Communication Technology), most of the worldwide defense operations, including the North Atlantic Treaty Organization (NATO) operations, are significantly relying on the space support services. One of the most essential services is the Positioning, Navigation and Timing (PNT) service, which is currently provided by the United States’ Global Positioning System (GPS). The GPS has become a global utility comparable to the internet, and it does not ‘just’ provide positioning data, but also provides the most important civilian/military use of the timing signal, which synchronizes all the communication and the encryption in all operations. While the USA has formulated first requirements to strengthen the resiliency of GPS in terms of the availability of accuracy, the availability of integrity and the availability of continuity, NATO has additional options to improve resiliency by integrating the European Galileo constellation. This paper focus mainly on the military implications of these two Global Navigation Satellite Systems (GNSS), to order to enrich the knowledge of the NATO members and policymakers about the PNT options available to the alliance, as well as addressing the various threats and challenges facing the PNT services.